2016
DOI: 10.1515/jppr-2016-0010
|View full text |Cite
|
Sign up to set email alerts
|

The role of detoxifying enzymes in the resistance of the cowpea aphid (Aphis craccivora Koch) to thiamethoxam

Abstract: The cowpea aphid (Aphis craccivora Koch) is considered a serious insect pest attacking several crops. We carried out biochemical studies to elucidate the role of the metabolising enzymes in conferring resistance to thiamethoxam, in two strains (resistant and susceptible) of the cowpea aphid. Bioassay experiments showed that the thiamethoxam selected strain developed a 48 fold resistance after consecutive selection with thiamethoxam for 12 generations. This resistant strain also exhibited cross-resistance to th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
12
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 24 publications
2
12
0
Order By: Relevance
“…On the other hand the P-450 apparently showed minor role in insects resistance to neonicotinoides. This result agrees with Koo et al (2014) and Abdallah et al (2016) who noted that no effect of P-450 in the IMI and THIA resistant strains of A. gossypii were found when using either synergists or a determination of the enzyme activity. In contrast, by using specific enzyme inhibitors, Zhu et al (2017) demonstrated that honey bees mainly rely on P-450s for detoxifying IMI, while esterases play substantially less roles in the detoxification.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…On the other hand the P-450 apparently showed minor role in insects resistance to neonicotinoides. This result agrees with Koo et al (2014) and Abdallah et al (2016) who noted that no effect of P-450 in the IMI and THIA resistant strains of A. gossypii were found when using either synergists or a determination of the enzyme activity. In contrast, by using specific enzyme inhibitors, Zhu et al (2017) demonstrated that honey bees mainly rely on P-450s for detoxifying IMI, while esterases play substantially less roles in the detoxification.…”
Section: Discussionsupporting
confidence: 91%
“…THIA is the second generation of neonicotinoids and belongs to thianicotinyl subclass while, IMI is the first generation and belongs to chloronicotinyls subclass Shi et al (2011). THIA and IMI provide excellent effect against a broad range of insects with sucking and chewing habits Jeschke and Nauen (2008) such as leaf miners as well as some lepidopterous species, aphids, Colorado potato beetle, whiteflies, fleas, beetles, wireworms, rice hoppers and thrips Abdallah et al (2016). They are also extensively used in control of insect pests of public health and agricultural importance Li et al (2012).…”
Section: Introductionmentioning
confidence: 99%
“…This means that esterase plays the key role in the resistance mechanism of R strain, followed by monooxygenases. The greater activity of detoxifying enzymes, particularly carboxylesterase has a significant role in endowing resistance to thiamethoxamin in the cowpea aphid (Abdallah et al 2016). These results agree with Fouad et al (2016) who found that esterase activity in three field populations of cowpea aphid was higher than in the susceptible strain.…”
Section: Discussionsupporting
confidence: 87%
“…This could partly be attributed to the low number of natural enemies recorded in the plots treated with Duduthrin ® . We also hypothesize that there could be possible aspects of resistance which has not been previously reported, since aphid species are known to develop resistance against insecticides after years of exposure (Abdallah, Abou‐Yousef, Fouad, & Kandil, ; Van Emden & Harrington, ). Similar observations on the population explosion of aphid species after use of Karate, a synthetic insecticide with same active ingredient (Lambda‐cyhalothrin) as Duduthrin ® , were earlier reported (Bayissa, ).…”
Section: Discussionmentioning
confidence: 91%